Sex, Gender, and Refugee Protection in Canada under Bill C-11: Are Additional Protections Required in Light of In re R-A-? - Tie, Chantal (Refuge: Canada’s Journal on Refugees, 2001)
This case comment takes a critical Canadian look at gender-based refugee claims in light of the recent United States Board of Immigration Appeals decision in re R-A-. The author points out that many of the obstacles for women who are refugee claimants in the United States, which are highlighted in re R-A-, also exist in Canada. She argues that when we are forced to define women’s gender persecution as persecution on account of “membership in a particular social group,” analytical problems are inevitable. These problems arise because our refugee definition does not acknowledge that women are persecuted worldwide simply because of their gender. The author urges that gender persecution be specifically included in the Canadian refugee definition, to bring the definition in line with other domestic and international human rights instruments, which already recognize the importance of women’s human rights.